A study of Polycyclic Aromatic Hydrocarbons (PAHs) and Trace Elements in Ambient air PM2.5 in an Urban Site of Tehran, Iran - Majid Kermani; Zahra Asadgol; Hossein Arfaeinia (Iranian Journal of Health, Safety and Environment, 2018)
The concentrations of thirteen polycyclic aromatic hydrocarbons (PAHs) and six trace elements adsorbed to a fine fraction of particulate matter (PM ≤ 2.5 µm) were determined at an urban site in Tehran (Iran) during the spring period in 2013. The average concentration of PM2.5 was 41.19 µg/m3, which was 1.64 and 1.2 times higher than the annual average of WHO guidelines and EPA ambient air quality standards, respectively. The trace elements measured in the PM2.5 samples were Pb, Cd, Cr, Ni, As and Zn with the mean concentrations of 38.05, 18.2, 4.24, 4.19, 1.34, and 69:92 ng/m3 respectively. Hg wasnot found in any sample in this study. Results from correlation tests between PM2.5 concentrations and different toxic metals; which were studied in various days of the week, including holidays, 1 day after the holidays, and the other days showed that the variability between groups were significant at the 0.05 level. Exception is Hg and Zn. The mean concentrations of PM2.5 and trace elements in 1 day after the holidays were higher compared other 2 groups. Total PAHs concentrations in PM2.5 were found to be 7.92 ng/m3.The most abundant PAHs found were high molecular weight homologues (4-6 ring PAHs) such as Inp, Bgp, Dba, Bkf and Bbf, which are contributing to constituents of vehicular emissions. In general, high molecular weight PAHs are more correlated than low molecular weight PAHs. Moreover a moderate correlation was observed between total PAH concentration and PM2.5 mass.